Nerve Entrapment Syndromes at the Wrist and Elbow by Sonography - Klauser, Andrea S.; Buzzegoli, Tommaso; Taljanovic, Mihra S.; Strobl, Sylvia; Rauch, Stefan; Teh, James; Wanschitz, Julia; Löscher, Wolfgang; Martinoli, Carlo (Seminars in Musculoskeletal Radiology, 2018)
Nerve entrapment syndromes of the upper extremity are associated with structural abnormalities or by an intrinsic abnormality of the nerve. Nerve entrapment syndromes generally have a typical clinical presentation, and findings on physical examination and in conjunction with electrodiagnostic studies imaging is used to evaluate the cause, severity, and etiology of the entrapment. With the development of high-frequency linear array transducers (12–24 MHz), ultrasound (US) is incomparable in terms of spatial resolution to depict morphological aspects and changes in nerves. US can identify the abnormalities causing entrapment, such as fibrous bands, ganglia, anomalous muscles, and osseous deformities, with the advantage of dynamic assessment under active and passive examination. US is a unique diagnostic modality that allows superb visualization of both large and small peripheral terminal nerve branches of the upper extremity and enables the correct diagnosis of various nerve entrapment syndromes.
Keywords: nerve entrapment; median nerve; radial nerve; ulnar nerve; sonography